2019
DOI: 10.1093/nar/gkz149
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis 6C sRNA binds multiple mRNA targets via C-rich loops independent of RNA chaperones

Abstract: Bacterial small regulatory RNAs (sRNAs) are the most abundant class of post-transcriptional regulators and have been well studied in Gram-negative bacteria. Little is known about the functions and mechanisms of sRNAs in high GC Gram-positive bacteria including Mycobacterium and Streptomyces . Here, we performed an in-depth study of 6C sRNA of Mycobacterium tuberculosis , which is conserved among high GC Gram-positive bacteria. Forty-seven gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 64 publications
7
65
1
Order By: Relevance
“…Our cross‐species genome sequence similarity analysis revealed that the B11 gene locus is highly conserved in the Mycobacterium genus (Appendix 2, Figure A4a) and in many representative members of other genera of Actinobacteria (not shown). These findings are consistent with reported analyses (DiChiara et al, ; Mai et al, ; Weinberg et al, ). The conservation of this gene suggests that its sRNA product has a critical function in the biology of Actinobacteria .…”
Section: Resultssupporting
confidence: 92%
“…Our cross‐species genome sequence similarity analysis revealed that the B11 gene locus is highly conserved in the Mycobacterium genus (Appendix 2, Figure A4a) and in many representative members of other genera of Actinobacteria (not shown). These findings are consistent with reported analyses (DiChiara et al, ; Mai et al, ; Weinberg et al, ). The conservation of this gene suggests that its sRNA product has a critical function in the biology of Actinobacteria .…”
Section: Resultssupporting
confidence: 92%
“…The role of sRNAs has been long established, and there is a growing body of knowledge on the topic. However, as reported by Mai et al (2019), there are considerable gaps of knowledge regarding small regulatory RNAs. The field has discovered until now a wide set of these molecules, but bigger efforts to elucidate their molecular mechanisms of action are needed.…”
Section: Respiratory Diseasesmentioning
confidence: 99%
“…The field has discovered until now a wide set of these molecules, but bigger efforts to elucidate their molecular mechanisms of action are needed. The sRNA 6C (six cytosine residues) was hypothesized, by the authors of this study, to play an important role in regulation of cell division of Mycobacterium tuberculosis (M. tb) (Mai et al, 2019). In their experiments, the authors used a vector to overexpress 6C sRNA of M. tb, and transformed Mycobacterium smegmatis.…”
Section: Respiratory Diseasesmentioning
confidence: 99%
“…It also has been observed that overexpression of some sRNAs leads to slow or delayed growth in mycobacteria (Arnvig & Young, 2009;Ignatov et al, 2015). Roles for the sRNAs Mcr7, MsrI and 6C/B11 in gene regulation in Mtb or Mycobacterium smegmatis (Msm) have been reported (Gerrick et al, 2018;Mai et al, 2019;Solans et al, 2014). However, the importance of these differentially expressed sRNAs to the adaptation and survival of Mtb during periods of stress has not been fully addressed.…”
Section: Introductionmentioning
confidence: 99%